Development of Alkali Metal through the Ashing of Rice Husk and Kenaf - Suppiah, Avieneish (IRC, 2017)
This study focuses on determination of the presence and concentration of metal present in rice husk and kenaf after incineration at different temperatures. The rice husk and kenaf are known to be the biggest mill generated biomass. The biomass is cleared by burning the rice husk and kenaf with the steam generator to reduce the input and cost of fuel that enters the engine. However, uncontrolled open burning of rice husk and kenaf results in many environmental and health danger and can jeopardise human, animal and plants substantially. On the other hand, uncontrolled burning of rice husk and kenaf causes metal oxides that accumulate in the furnaces and cause the efficiency of the furnace to reduce. The reduction of the efficiency causes more maintenance cost and lesser productivity of the company. Hence, this study helps us determine the metals that are present in the rice husk and kenaf to find out a way of elimination to reduce maintenance time of the furnace itself. The rice husk and kenaf collected are being burned at three different temperatures; 530ᴼC, 570ᴼC and 600ᴼC to find out the concentration of metals that are present in the ashes. The ash is then liquefied and filtered to clear solution before entering the ICP-AES machine to determine the concentration of each metal element that are present in the RHA and kenaf ash. The results are predicted of the presences of the metal element even though the concentration will be investigated and analysed in the report with relation to slagging index is also analysed.